Detailed guidance for issuing green bonds in developing countries - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
Provides guidance for bond issuers and their advisors on the process and key considerations for a successful green bond issuance. This publication covers all the steps required to follow best practices in labeling bonds as green. It includes examples, links to further details, and key resources for green bond issuers and their deal teams.
Introduction - - About This Guidance Note - - Identifying Green Projects, Assets, and Expenditures - - Developing a Green Bond or Sustainable Finance Framework - - Confirming Internal Processes and Controls - - Reporting on Allocations and Green Credentials - - Setting Up for Impact Reporting - - Engaging the External Reviewer - - Managing the External Review Process - - Seeking Certification or Recognition - - Media, Stakeholders, Indices, and Listings - - Post-Issuance Reporting and Disclosure - - Further Issuance of Labeled Instruments.
Keywords: Bonds; Bond market -- Developing countries; Corporate bonds